Por que as tarifas de interconexão são tão altas? Um modelo de competição entre telefonia fixa e móvel - Lima, Lucas Ferreira Matos (2014)
There is a puzzle between the literature of competition of telecommunication networks and the reality. The first one has as the main result that the mobile termination rates will be set bellow the marginal cost to end a call. But the reality shows that the mobile termination rates are too high and the regulators faces a lot of constrains when they try to bring down the level of those rates, because the mobile networks oppose to those policies. This work develops a model based on Hoernig (2010) that presents more realistic results. It will use a new assumption: the mobile networks will compete at the same market with a fixed network and this last one will have its prices regulated. This is a plausible assumption considering the actual development of the mobile networks. The model has two frameworks: at the first there is any kind of shared control between one of the mobile and fixed telephony, but at the second that shared control exists. Because of the assumption that the mobile and fixed networks will compete, this work has as general result that the mobile networks will set the mobile termination rates above the marginal cost of terminating a call.